2021
DOI: 10.1111/jerd.12743
|View full text |Cite
|
Sign up to set email alerts
|

Natural antioxidants to restore immediate bond strength to bleached enamel: Systematic review and meta‐analysis of in vitro studies

Abstract: Objective To evaluate whether natural antioxidant treatment would enhance the immediate bond strength of dental adhesives to bleached enamel through a systematic review and meta‐analysis. Materials and methods Two reviewers performed a literature search up to November 2019 in seven databases. Only in vitro studies that evaluated the effect of the application of natural antioxidants in the bond strength of dental adhesives to bleached enamel were included. Analyses were carried out using RevMan 5.3.5 (The Nordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…The present findings are in agreement with some studies that reported no harmful effect on the bond strength of restorations bonded to teeth after at-home bleaching [ 30 – 33 , 39 , 40 ]. In contrast, several studies indicated lower adhesion strength in teeth recently exposed to professional bleaching procedures [ 18 , 23 , 41 43 ]. The investigations on the use of whitening dentifrices on bond strength also reported controversial results, with some studies reporting detrimental effects [ 7 , 11 , 14 ], whereas others showed comparable [ 9 , 44 ] or even higher [ 45 ] bonding values as compared to regular dentifrices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings are in agreement with some studies that reported no harmful effect on the bond strength of restorations bonded to teeth after at-home bleaching [ 30 – 33 , 39 , 40 ]. In contrast, several studies indicated lower adhesion strength in teeth recently exposed to professional bleaching procedures [ 18 , 23 , 41 43 ]. The investigations on the use of whitening dentifrices on bond strength also reported controversial results, with some studies reporting detrimental effects [ 7 , 11 , 14 ], whereas others showed comparable [ 9 , 44 ] or even higher [ 45 ] bonding values as compared to regular dentifrices.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been suggested to neutralize and reverse the effects of bleaching agents on bond strength such as delaying the restorative procedures up to 2 weeks after whitening [17][18][19] or treatment of the tooth surface with chemicals such as sodium ascorbate (a potent antioxidant), catalase, ethanol or water to dissociate residual peroxides and oxygen free radicals from the substrate [13,[20][21][22][23]. Another option to enhance the bond strength may be the increase in the polymerization time of adhesive systems.…”
Section: Introductionmentioning
confidence: 99%
“…Using antioxidants appears to be the best, fastest, and most convenient way of reversing the decreased bond after bleaching (Leandrin et al, 2020;Olmedo et al, 2021;Pooja et al, 2021;Rodríguez-Barragué et al, 2021;Shamsedin et al, 2017;Y. X. Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Using antioxidants appears to be the best, fastest, and most convenient way of reversing the decreased bond after bleaching (Leandrin et al, 2020 ; Olmedo et al, 2021 ; Pooja et al, 2021 ; Rodríguez‐Barragué et al, 2021 ; Shamsedin et al, 2017 ; Y. X. Xu et al, 2021 ). The results of the present study demonstrated that none of the antioxidant solutions reestablish the compromised bond strength in the bleached enamel.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of GSE and PBE can be attributed to the multiple donor sites found on its OPC which have a specificity for trapping the superoxide and hydroxyl free radicals which enhances free radical scavenging and increases the bond strength of composite to bleached enamel [18].…”
Section: Discussionmentioning
confidence: 99%